2012
DOI: 10.1093/humupd/dmr052
|View full text |Cite
|
Sign up to set email alerts
|

The ESHRE PGD Consortium: 10 years of data collection

Abstract: In this paper, we present an overview of the first 10 years of PGD data, highlighting trends. These include the introduction of laser-assisted biopsy, an increase in polar body and trophectoderm biopsy, new strategies, methodologies and technologies for diagnosis, including recently arrays, and the more frequent use of freezing biopsied embryos. The Consortium data reports represent a valuable resource for information about the practice of PGD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
211
2
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(226 citation statements)
references
References 45 publications
8
211
2
4
Order By: Relevance
“…Although PGD can be used for almost all genetic disorders with a recognized mutation, allele dropout (ADO), where one of the two alleles is preferentially amplified and the other allele is amplified under a detectable level, is the primary inherent pitfall of single-cell PCR and can lead to misdiagnoses [17,18]. For autosomal dominant disorders, ADO of the affected allele would cause a serious misdiagnosis for the transfer of an affected embryo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PGD can be used for almost all genetic disorders with a recognized mutation, allele dropout (ADO), where one of the two alleles is preferentially amplified and the other allele is amplified under a detectable level, is the primary inherent pitfall of single-cell PCR and can lead to misdiagnoses [17,18]. For autosomal dominant disorders, ADO of the affected allele would cause a serious misdiagnosis for the transfer of an affected embryo.…”
Section: Discussionmentioning
confidence: 99%
“…Although PGD has been applied successfully in the clinic, misdiagnoses discovered by prenatal diagnosis have been reported [2,18]. The European Society of Human Reproduction and Embryology (ESHRE) PGD consortium reported that the misdiagnosis rates of the PCR-based and FISH-based PGD cycles were 0.14 % (13/9317) and 0.06 % (21/34,855), respectively [2].…”
Section: Discussionmentioning
confidence: 99%
“…PGS at day 3 of development counting 5 to 9 chromosomes with fluorescent in situ hybridization (FISH) in one biopsied cell knew a high flight in the nineties of last century, and the early years of this century [6] and was at some point more frequently performed than PGD. The practice of PGS was mainly supported by non-randomized studies with poor experimental design and inadequate control groups [7], and by 2010, 11 randomized controlled trials (RCTs) had been published that demonstrated that PGS did not increase, and in some cases even decreased, pregnancy rates [6]. With hindsight, that first version of PGS may not have worked because only a handful of chromosomes were counted, while all chromosomes seem to be affected in preimplantation embryos [8].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 According to 10 years of data collection by the ESHRE PGD Consortium, PGD has been applied to over 190 different monogenic disorders. 3 Currently all methods for PGD to exclude monogenic diseases are based on the polymerase chain reaction (PCR), with or without prior whole-genome amplification. Genetic analysis may be performed at various stages post fertilization, including the oocyte/zygote biopsied on the first day postinsemination (polar body analysis), on 1-2 blastomeres from cleavage-stage embryos biopsied on the third day post-insemination (blastomere biopsy) or on 5-10 trophectoderm cells biopsied from blastocysts on the fifth day post-insemination (blastocyst biopsy).…”
Section: Introductionmentioning
confidence: 99%
“…During 10 years of data collection recording the outcome of over 4700 cycles for monogenic PGD, 12 adverse misdiagnoses were reported. 3,4 However, this is probably an underestimation, as many embryo transfers have no follow up (no pregnancy or birth). Furthermore, based on a survey done amongst ESHRE PGD consortium members in 2008 (unpublished results), only a minority of centres perform reanalysis of untransferred supernumerary embryos.…”
Section: Introductionmentioning
confidence: 99%